Oral Intake and Topical Application of Hyaluronic Acid Ameliorates Skin Aging Signs: Efficacy Results of a Placebo-Controlled In&Out Trial - Vincenzo Nobile; Gloria Roveda; Eleonora Spartà; Francesco Tursi (Cosmetics)
Hyaluronic acid (HA) content in the skin progressively decreases with age; thus, its supplementation—either topical, oral, and by subcutaneous injection—represents a first-line intervention to ameliorate skin aging signs. The present multicenter randomized placebo-controlled trial (RCT) evaluated the skin antiaging efficacy of an In&Out treatment, i.e., a concomitant topical, through a cosmetic cream, and the oral administration of specifically designed HAs, full-spectrum HAs (FS-HAs), in a multiethnic population using instrumental measurements and clinical assessments. The efficacy of FS-HAs was also evaluated in groups receiving FS-HA in a single administration route and in the presence of the placebo in the counterpart route. The above treatment scheme was applied for 56 days to 88 adult subjects, equally divided into four groups. Treatments containing at least one FS-HA molecule showed progressive and significant intragroup ameliorations of all the instrumental skin parameters evaluated. The In&Out treatment resulted in a greater improvement with respect to the two other active groups and in significant intergroup differences with respect to its placebo counterpart. FS-HA treatments resulted, as well, in the significant improvements of clinical parameters that correlated with the subjects’ appreciation recorded by a self-assessment, hence confirming that the In&Out administration of FS-HA represents an interesting approach to counteract skin aging signs.